Case reportRing annuloplasty and successful mitral valve repair in a staphylococcal endocarditis case with bilobular saccular mycotic aneurysm at cerebral artery and frontal region infarction. Secondary to septic emboli - Özbek, Cengiz; Yetkin, Ufuk; Bademci, Mehmet; Karahan, Nagihan; Gürbüz, Ali (Archives of Medical Science, 2008)
Staphylococcus is the aetiological agent in 1/3 of infective endocarditis(IE) cases. It has a high virulence and prognosis is poor due to severe intracardiac injury and frequent embolic complications. Leaflets are the most frequently affected part in mitral valve endocarditis. Following the endocarditis, many structural anomalies such as vegetations, destruction, regurgitation and calcific deposits on leaflets can develop. Embolism due to vegetations or infected tissues is the most frequent complication and is closely related to prognosis. Post mortem studies have shown that the brain embolization rate is up to 40%. Our case was a methicillin-sensitive coagulase negative staphylococcal (MSCONS) IE and had two very rare cerebral complications. We present our diagnostic approach and successful mitral valve repair technique. Surgery for infective endocarditis is potentially life saving. Successful management requires a multidisciplinary approach involving microbiologists, cardiologists, and cardiothoracic surgeons. Frequency of staphylococcal endocarditis has increased progressively in the last twenty years. Medical treatment alone is not sufficient for radical therapy and surgery is necessary. Antibiotic and surgery combination is the best and most effective treatment method. Survival is positively affected and quality of life is increased in long term.